Pollen and fungal remains as environmental indicators in surface sediments of Isla Grande de Tierra del Fuego, southernmost Patagonia - Musotto, Lorena Laura (2012)
Palynological studies have been performed in order to increase knowledge of relations between present vegetation and fungal biota. The analysis of modern analogues will help to improve the palaeoenvironmental reconstructions of fossil sequences from Isla Grande de Tierra del Fuego. A total of 24 fungal taxa have been found, described and illustrated. Surface samples were collected from the different vegetation communities developed on the island: steppe, Nothofagus forest–steppe ecotone and Nothofagus forest. The steppe is characterised by a predominance of Poaceae pollen accompanied by Nothofagus pollen (up to 30%) and spores of Glomus sp. In the forest–steppe ecotone, Nothofagus pollen frequencies rise up to 50% along with dwarf shrub heath communities and Gaeumannomyces species. In the forest unit, the percentage values of Nothofagus pollen surpass 50%. Among the fungal remains, fructifications of Microthyriaceae and dematiaceous spores such as Alternaria sp., Dictyosporium sp. and Sporidesmium sp. are present in forest samples and may be related to damp environments. Ascospores of the coprophilous Sordaria-type and Sporormiella-type appear to be common and are probably associated with livestock grazing. Fungal remains are very scarce in some of the samples obtained in mire environments. The ecological requirements of some of the fungi identified allowed inferences about the local conditions of the sampled site. This study demonstrates the palaeoenvironmental indicator value of fungal components and encourages further investigation of surface samples considering local habitat features to obtain a better understanding of local environmental conditions in the past.